Efforts to Improve Student learning Outcomes Using Cooperatif Learning Models in Theme III Interview Question Writing Materials Using Connection and Preservation of Class IV Natural Resources SDN 1 Candinata Study Year 2020/2021 - Emi Widyaningsih (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve student learning outcomes in learning theme 3 in grade IV elementary schools using Cooperatif learning models. The research conducted was a Classroom Action Research (CAR) consisting of three cycles. The stages of each cycle were planning, implementing, observing and reflecting. Each meeting is carried out an assessment of knowledge, skills and attitudes to determine the development of students. In cycle I, students who completed after carrying out the knowledge assessment were 69%. In cycle II students who completed after carrying out the knowledge assessment were 84%. In cycle III students who completed after carrying out the knowledge assessment were 93%. These results indicate that the use of video media can improve student learning outcomes, especially the theme of Class IV at SDN 1 Candinata.